Troubleshooting Engine Overheat on Wheel Loader Liugong Type 856H - Raihan Trinanda Agsya; Shafa Nisrina; Rahmat Noval; Hong Yue; Andrian Pratama Batistuta; Seto Aji Santoso (Recent in Engineering Science and Technology, 2024)
The Liugong type 856H Wheel Loader unit was donated by PT. Liugong Machinery to Liuzhou Vocational and Technical College (LVTC) as part of a collaborative effort to support teaching and learning activities at LVTC. During practical use, this Wheel Loader unit experienced engine overheating. The aim of troubleshooting the engine overheating issue was to identify the root cause of the problem. This research was conducted using direct observation methods, specifically employing a 7-step troubleshooting approach. The research findings indicate that the engine overheating in the Liugong type 856H Wheel Loader unit was caused by a malfunctioning thermostat component. According to specifications, the thermostat should begin to open at a temperature of 78°C and fully open at 92°C. However, upon inspection, the thermostat did not open until the temperature reached 90°C. This prevented coolant from flowing to the radiator for cooling. As a result, the hot coolant continued to circulate within the engine, leading to engine overheating. The corrective action taken was to replace the faulty component.